A Neurophenomenology of Awe and Wonder : Towards a Non-Reductionist Cognitive Science /: Towards a Non-Reductionist Cognitive Science. (2015) - Gallagher, Shaun; Professor, Janz, Bruce; Dr, Reinerman, Lauren; Bockelman, Patricia; Trempler, Jörg
No abstract available